ANALYSIS OF EFFECTIVENESS OF ADVERTISING ABOVE THE LINE AND BELOW THE LINE ON THE CUSTOMERS PURCHASE DECISION - ANDI HASRYNINGSIH ASFAR; SONDI (AKADEMIKA, 2019)
Sedaap Noodle is a product of PT. Sayap Mas Utama, which has a low number of sales, especially in the Cilegon City area, allowing Above The Line and Below The Line advertising promotion activities.This study aims to analyze the effectiveness of advertising above the line and below the line on customer purchasing decisions of Sedaap Noodle products in the area of Cilegon-Banten City. This study uses two independent variables, namely above the line and below the line advertising, one dependent variable is the purchase decision. This research was conducted on the customer population of Sedaap Noodle products in the area of Cilegon-Banten City with a total sample of 96 respondents. The type of research used is qualitative research with the Simple Random Sampling approach. The method used in measuring the effectiveness of advertising above the line and below the line uses EPIC Model, Direct Rating Method and Linear Regression with the help of Minitab 16 software. Based on the measurement using EPIC Model, the EPIC Rate of promotion above the line score is 3.993, while the below the line promotion gets a value of 3.955, this explains that the above the line promotion is more effective than the below the line promotion. As for the measurement using the Direct Rating Method (DRM) method, the above the line promotion value is 71.40 and the below the line promotion gets a value of 66.42 where the value falls into the "good" scale.Of the two calculation methods that can be used for this type of promotion above the line is the type of promotion that is the best and most effective in determining the purchase decision of Sedaap Noodle products in the Cilegon-Banten City area and the type of advertising promotion above that line. with the media used with 92%.